Latest advance anti-inflammatory hydrogel wound dressings and traditional Lignosus rhinoceros used for wound healing agents - Arbab, Safia; Ullah, Hanif; Muhammad, Nehaz; Wang, Weiwei; Zhang, Jiyu (Frontiers in Bioengineering and Biotechnology, 2024)
Wound healing is a physiological process occurring after the onset of a skin lesion aiming to reconstruct the dermal barrier between the external environment and the body. Depending on the nature and duration of the healing process, wounds are classified as acute (e.g., trauma, surgical wounds) and chronic (e.g., diabetic ulcers) wounds. The latter, often affect millions of people globally, take months to heal or not heal non-healing chronic wounds, are typically susceptible to microbial infection, and are a major cause of morbidity. Wounds can be treated with a variety of non-surgical (topical formulations, wound dressings) and surgical (debridement, skin grafts/flaps) methods. Three-dimensional (3D)-(bio) printing and traditional wound dressings are two examples of modern experimental techniques. This review focuses on several types of anti-inflammatory wound dressings, especially focusing on hydrogels and traditional macro-fungi like L. rhinocerotis as agents that promote wound healing. In this study, we introduced novel anti-inflammatory hydrogel dressings and offered innovative methods for application and preparation to aid in the healing. Additionally, we summarize the key elements required for wound healing and discuss our analysis of potential future issues. These findings suggest that L. rhinocerotis and various anti-inflammatory hydrogels can be considered as conventional and alternative macro-fungi for the treatment of non-communicable diseases. We summarized the development of functional hydrogel dressings and traditional Lignosus rhinoceros used for wound healing agents in recent years, as well as the current situation and future trends, in light of their preparation mechanisms and functional effects.